How is sound conducted to the cochlea in toothed whales? - Zosuls, A.; Mountain, D.; Ketten, Darlene (2015)
© 2015 AIP Publishing LLC. Toothed whales (Odontocetes) typically have small occluded ear canals and sea water has a characteristic impedance that is much more similar to the impedance of soft tissues of the head than is the case for the air-tissue interface in terrestrial mammals. This makes it plausible that significant acoustic energy is being transmitted to their middle ear by tissue conduction. In addition, some authors have proposed that sound reaches the cochlea via bone conduction rather than via the tympanic membrane. To address these issues, we have developed a method to measure stapes velocity in response to vibrational stimulation at arbitrary locations on heads and ears harvested from stranded animals. Stapes velocity was measured with a Laser Doppler Velocimeter at the footplate with the cochlea drained. In all species tested, the transfer function of stapes velocity referenced to actuator velocity showed a high-pass characteristic. The corner frequency varied with species and experiment between 4 kHz and 60 kHz. This is similar to what is seen in odontocete audiograms but the cutoff slope is typically steeper than in the audiograms. There was no indication of high frequency cutoff within our measurement range. Disrupting the ossicles and fat bodies affected the transfer functions.